PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA SATUAN KERJA PELAKSANAAN JALAN NASIONAL WILAYAH II PROVINSI JAWA TIMUR - Trilaksono, Suryo Purnomo; Rahayu, Sri; Setiadi, Pompong B.; Fitrianty, Rifda (MANAJEMEN DEWANTARA, 2024)
It was found that employees were not present on time, employees were not present during working hours, service was still slow, and there were many other complaints from the public. This research was conducted to find out: (1) the impact of motivation on employee performance in the National Road Implementation Work Unit Region II, East Java Province, (2) the impact of work discipline on employee performance in the National Road Implementation Work Unit Region II, East Java Province. This research includes causality research using a quantitative approach. The research population consisted of 35 employees of the National Road Implementation Work Unit Region II of East Java Province. Data was obtained using a questionnaire whose validity and reliability have been tested. The data analysis method used is multiple regression. The results of this research provide data that: (1) Motivation has a positive impact on employee performance at the Regional II National Road Implementation Work Unit Office, East Jav); (2) Work discipline has a positive effect on the performance of employees of the National Road Implementation Work Unit Region II of East Java Province